L’innovation et le modèle du commerce néo-technologique dans l’espace des caractéristiques de Lancaster - Hanel, Petr (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
Lancaster's case of innovation in consumption technology is formalized and extended to include beside of the criterion of efficient consumption also the criterion of efficient production. The two criteria has to be met before an invention can be commercialized economically. Trade provoked by an innovation in consumption technology—a new product—is analyzed on a simple numerical example. Necessary conditions and some welfare implications of the neo-technology trade are presented. The approach is sufficiently general to encompass trade based on cost reducing innovation as well as existing trade models as special cases.